Early Efficacy of Intra-Articular HYADD® 4 (Hymovis®) Injections for Symptomatic Knee Osteoarthritis - Priano, Ferdinando (Joints, 2017)
Purpose The aim of the study was to evaluate the clinical effects of HYADD® 4, an hydrogel based on a hyaluronic acid derivative, in patients with symptomatic knee osteoarthritis, on symptoms, and joint function.Methods This retrospective study of patients with Kellgren–Lawrence grade II to IV knee osteoarthritis (American College of Rheumatology criteria) enrolled patients who had received two infiltrations of HYADD® 4, (24 mg/3 mL) 1 week apart, and evaluated: pain at rest, pain with movement, change in Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score; change in nonsteroidal anti-inflammatory drugs (NSAIDs)/acetaminophen use; satisfaction with therapy; tolerability. Study duration was 6 months for all predefined endpoints, with a 6-month extension for pain symptoms only.Results After 6 months, all predefined endpoints were evaluable in 698 of 937 enrolled patients (74.5%). Mean WOMAC scores were reduced by 56.3% from baseline (p < 0.05). NSAIDs/acetaminophen use ≥2 times/week (48.8% of patients at baseline) was substantially reduced after 1 month and was 19.6% after 6 months. After 6 months, 85.6% of patients were satisfied about efficacy. There were no significant adverse effects. The effect on resting pain was rapid, strong, and lasting: reduction from baseline was 45.1% at 1 month (p < 0.05), 56.8% at 6 months (p < 0.05), and 53.6% at 12 months (p < 0.05). Pain on moving was reduced by 47.4% after 6 months (p < 0.05) and 46.0% after 12 months (p < 0.05), results at 6 and 12 months were similar.Conclusion HYADD® 4 is a new-generation hyaluronic acid with distinctive viscoelastic and rheological properties. In patients with mild-to-severe knee OA (Kellgren–Lawrence grades II–IV), two consecutive infiltrations 1 week apart reduced WOMAC scores and NSAIDs/acetaminophen consumption for at least 6 months. In a subpopulation (n = 106), efficacy on pain lasted approximately 12 months. Adverse events were reported in 11.2% of patients; the most frequent were arthralgias. No cases of allergic reactions or systemic effects were recorded.Level of Evidence Level IV, retrospective case series.
Keywords: hyaluronic acid; osteoarthritis; knee; viscosupplementation; Hymovis®; viscoelastic